The effect of IFRS adoption and law enforcement on book tax aggressiveness: Evidence from Asean countries - Theresia Woro Damayanti (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
Firms are arguably motivated to exhibit tax aggressiveness because tax constitutes a significant portion of firms' total costs. This study aims to test the effects of IFRS adoption and law enforcement on book-tax aggressiveness in six developing ASEAN countries. Our sample is 29,504 firm-year observations generated from Thomson Reuters Eikon for the years 2000-2017. The results show that IFRS adoption has a positive effect on book-tax aggressiveness, indicating that firms tend to prioritize book-tax aggressiveness over book-tax conformity. Further, law enforcement negatively affects book-tax aggressiveness. All in all, our findings imply that law enforcement is very crucial for ASEAN countries to enhance managers' awareness of not engaging the book-tax aggressiveness practice.
Keywords: M41; H25; H26; 650; tax reporting aggressiveness; financial reporting aggressiveness; IFRS; law enforcement